Participation in American culture and society - Löffler, Philipp; Peterfy, Margit; Rauscher, Natalie; Werner, Welf (American studies, 2024)
Cover -- Titel -- Imprint -- Contents -- Preface -- PHILIPP LÖFFLER, MARGIT PETERFY, NATALIE RAUSCHER, WELF WERNER: Introduction: Participation in Crisis? -- Section I: Politics and Society -- CAROL ANDERSON: One Person, No Vote: Rigging the Rules -- JUDY TZU-CHUN WU: Pacific Feminist Imaginaries: The 1977 US National Women's Conference and the Politics of Territorial Representation -- LAURA KETTEL: Unequal Streets: Homelessness, Public Space, and Exclusion in the American City -- SILKE BRASELMANN: Teaching About Black Lives Matter, Teaching Against Racism: Opportunities for Participation in Antiracist English Language Teacher Education -- HELEN A. GIBSON: Teaching Towards Calvin Warren's Nonmetaphysical Historiography -- Section II: Literary Studies and the Arts -- ANDREW ERICKSON: Refusing American History: Non-participation and Narrative Resistance in Ta-Nehisi Coates's ‚The Water Dancer' -- MARCEL HARTWIG: ‚Felon', Convict, Attorney: Reginald Dwayne Betts and the Poetics of Re-Entry -- MAGDA MAJEWSKA: The Literary Prestige of Censorship: The Case of ‚Naked Lunch' -- TIM LANZENDÖRFER: Participatory Literary Studies and the Question of Public Method -- KIRSTEN TWELBECK: Community Engagement and Participation in Wheatfield. A Confrontation -- Section III: Media Landscapes -- MARTIN BUTLER: The Audience Strikes Back… Or Does It? Formations of Participation and the Figure of the Amateur in New Media Environments -- JULIANN KNAUS: Participatory Platform versus Condemning Community: In/Exclusion in the Black Natural Hair Movement on YouTube -- LENA GOTTESWINTER: Appropriation as Participation: A 21ˢᵗ-Century Reshaping of the Cultural Memory of Hip -- TAMARA HEGER: Who gets to be a Liberator? Participation and Recognition in Robert W. Hacker's ‚Flossenbürg Concentration Camp' -- List of Contributors -- Backcover.
Description based on publisher supplied metadata and other sources
"This volume contains selected papers presented at the 67th annual conference of the German Association for American Studies (Deutsche Gesellschaft für Amerikastudien/DGfA), which was organized by the Heidelberg Center for American Studies (HCA) in June 2021 at Heidelberg University." - Vorwort
Keywords: Konferenzschrift; Partizipation; Bürgerbeteiligung; Politische Beteiligung; USA; Geschichte; Kultur; Literatur